Risk factors for ocular surface squamous neoplasia in Kenya: a case–control study. Issue 12 (24th October 2016) - Gichuhi, Stephen; Macharia, Ephantus; Kabiru, Joy; Zindamoyen, Alain M'bongo; Rono, Hillary; Ollando, Ernest; Wachira, Joseph; Munene, Rhoda; Onyuma, Timothy; Jaoko, Walter G.; Sagoo, Mandeep S.; Weiss, Helen A.; et al.
Abstract: Objective: To determine modifiable risk factors of ocular surface squamous neoplasia (OSSN) in Kenya using disease‐free controls. Methods: Adults with conjunctival lesions were recruited at four eye care centres in Kenya and underwent excision biopsy. An equal number of controls having surgery for conditions not affecting the conjunctiva and unrelated to ultraviolet light were group‐matched to cases by age group, sex and eye care centre. Associations of risk factors with OSSN were evaluated using multivariable logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs). Continuous variables were compared using the t‐test or the Wilcoxon–Mann–Whitney U ‐test depending on their distribution. Results: A total of 131 cases and 131 controls were recruited. About two‐thirds of participants were female, and the mean age of cases and controls was 42.1 years and 43.3 years, respectively. Risk factors for OSSN were HIV infection without antiretroviral therapy (ART) use (OR = 48.42; 95% CI: 7.73–303.31) and with ART use (OR = 19.16; 95% CI: 6.60–55.57), longer duration of exposure to the sun in the main occupation (6.9 h/day vs . 4.6 h/day, OR = 1.24; 95% CI: 1.10–1.40) and a history of allergic conjunctivitis (OR = 74.61; 95% CI: 8.08–688.91). Wearing hats was protective (OR = 0.22; 95% CI: 0.07–0.63). Conclusion: Measures to prevent and control HIV, reduce sun exposure such as wearing hats and control allergic conjunctivitis are recommended.